Hubungan Self-efficacy dan Kemampuan Literasi Numerasi Siswa: Ditinjau Berdasarkan Gender - Mellyzar Mellyzar; Ratna Unaida; Muliani Muliani; Nanda Novita (UIN AR-RANIRY, 2022)
Students with high self-efficacy mean having high motivation, awareness and self-regulation so that it is expected to have a positive effect on learning outcomes including numeracy skills, self-efficacy can be influenced by internal factors such as gender. This study aims to analyze differences in self-efficacy students' and numeracy literacy skills based on gender, the relationship between self-efficacy and students' numeracy literacy skills based on gender and the effect of self-efficacy on students' numeracy literacy skills. The method used is descriptive method. The sample of this study was 88 students consisting of 44 male students and 44 female students of VIII SMP from four schools in North Aceh and Lhokseumawe who were participants in the 2021 national assessment. Data collection used questionnaire instrument self-efficacy containing 45 statement items and 36 numeracy literacy questions that are already valid and in accordance with the AN question grid. The results showed that the significance value was 0.288 > 0.005 indicating that there was no significant difference between the self-efficacy of male and female students, (2) the significance value was 0.652 > 0.05, meaning that there was no significant difference between literacy abilities numeracy men and female (3) self-efficacy and literacy numeracy students have a relationship with the degree of correlation is high and positively related (4) the coefficient of determination (R2) of 0.489 explains that the influence of self-efficacy with literacy numeracy student is 48.9%.